Expectations, Uncertainty and Inventory Fluctuations - Mills, E. S. (Review of Economic Studies, 1954)
Journal Article Expectations, Uncertainty and Inventory Fluctuations Get access E. S. Mills E. S. Mills University College of North Staffordshire Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 1, 1954, Pages 15–22, https://doi.org/10.2307/2296220 Published: 01 January 1954